Impact of Interstitial Lung Abnormalities on Disease Expression and Outcomes in COPD or Emphysema: A Systematic Review - Liu Y; Tang J; Sun Y (International Journal of COPD, 2023)
Yujia Liu,1,2,* Jingyun Tang,3,* Yongchang Sun1 1Department of Respiratory and Critical Medicine, Peking University Third Hospital, Beijing, People’s Republic of China; 2Department of Respiratory and Critical Medicine, Peking University International Hospital, Beijing, People’s Republic of China; 3Blood Research Laboratory, Chengdu Blood Center, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongchang Sun, Department of Respiratory and Critical Medicine, Peking University Third Hospital, 49 North Garden Road, Haidian District Beijing, People’s Republic of China, Tel +86-010-82265020, Email suny@bjmu.edu.cnBackground: Both COPD and interstitial lung abnormalities (ILAs) are conditions associated with smoking and age. The impact of coexistent ILAs on the manifestations and outcomes of COPD or emphysema awaits evaluation.Methods: We searched PubMed and Embase using Medical Subject Headings terms in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Results: Eleven studies were included in the review. The sample size of the studies ranged from 30 to 9579. ILAs were reported in 6.5% to 25.7% of the patients with COPD/emphysema, higher than that reported in the general populations. COPD/emphysema patients with ILAs were older, mostly male, and had a higher smoking index than those without ILAs. Hospital admission and mortality were increased in COPD patients with ILAs compared to those without ILAs, whereas the frequency of COPD exacerbations was discrepant in 2 of the studies. The FEV1 and FEV1% predicted tended to be higher in the group with ILAs, but not significantly in most of the studies.Conclusion: ILAs were more frequent in subjects with COPD/emphysema than in the general population. ILAs may have a negative impact on hospital admission and mortality of COPD/emphysema. The impact of ILAs on lung functions and exacerbations of COPD/emphysema was discrepant in these studies. Further prospective studies are warranted to provide high-quality evidence of the association and interaction between COPD/emphysema and ILAs.Keywords: COPD, emphysema, interstitial lung abnormalities, review